ANTIBACTERIAL ACTIVITY, FREE RADICAL SCAVENGING POTENTIAL, PHYTOCHEMICAL INVESTIGATION AND IN-VIVO TOXICITY STUDIES OF MEDICINAL PLANT Embelia basaal (R. & S.) A. DC. - Barbade, Komal D; Datar, Ajit G (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Present extensive study on medicinal plant Embelia basaal (R. & S.) A. DC. was undertaken for evaluation and quantification of broad spectrum antibacterial activity, free radical scavenging potential, phytochemical investigation, development of high performance thin layer chromatography (HPTLC) fingerprint profile and in-vivo safety of the plant. Methods: Dried fruits of the plant were powdered and macerated in variety of solvents to obtain four extracts of different polarities. Antibacterial activity was evaluated using agar well diffusion assay. Most potent antibacterial extract of E. basaal was selected for further extensive studies. Minimum inhibitory concentration (MIC) values of the potent antibacterial extract were determined using broth macrodilution method as per Clinical Laboratory Standards Institute guidelines. Free radical scavenging activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl assay. Qualitative phytochemical tests, quantification of total phenolic contents and HPTLC fingerprint analysis were carried out for phytochemical investigation. The in-vivo safety of the plant was determined by conducting acute oral toxicity studies in mice as per Organization for Economic Co-operation and Development guidelines test no. 420. Results: Ethanol extract of E. basaal was found potent bactericidal against selected pathogens and chosen for further extensive studies. The extract exhibited significant free radical scavenging activity (inhibitory concentration 50 value=50 Î¼g/mL). Phytochemical investigation revealed presence of phenolic compounds, terpenoids, tannins and alkaloids in the test extract and it was found safe in-vivo at a dose level of 2000 mg/kg body weight of an animal. Conclusion: E. basaal was found medicinally active in the present study. Its broad spectrum antibacterial activity, significant free radical scavenging potential and in-vivo safety will provide a platform for advance studies in the area. Keywords: Embelia basaal (R. & S.) A. DC., Bactericidal activity, Free radical scavenging activity, Phytochemical investigation, High performance thin layer chromatography fingerprint, Acute oral toxicity.